2014
DOI: 10.1186/s13023-014-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of fragile X syndrome phenotypes in Fmr1KO mice by a BKCa channel opener molecule

Abstract: BackgroundFragile X Syndrome (FXS) is the most common form of inherited intellectual disability and is also associated with autism spectrum disorders. Previous studies implicated BKCa channels in the neuropathogenesis of FXS, but the main question was whether pharmacological BKCa stimulation would be able to rescue FXS neurobehavioral phenotypes.Methods and resultsWe used a selective BKCa channel opener molecule (BMS-204352) to address this issue in Fmr1 KO mice, modeling the FXS pathophysiology. In vitro, acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 54 publications
8
98
2
Order By: Relevance
“…Given the recent cessation of a number of prominent clinical trials aiming to treat FXS through established mechanistic procedures, we feel it is imperative to continue to investigate other mechanisms of FXS and new therapeutic strategies. Our work, together with previous findings 45 , suggests a strong therapeutic potential for BK Ca channel openers for the treatment of this disorder.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Given the recent cessation of a number of prominent clinical trials aiming to treat FXS through established mechanistic procedures, we feel it is imperative to continue to investigate other mechanisms of FXS and new therapeutic strategies. Our work, together with previous findings 45 , suggests a strong therapeutic potential for BK Ca channel openers for the treatment of this disorder.…”
Section: Discussionsupporting
confidence: 58%
“…We then tested whether a BK Ca channel opener could correct this defect in another batch of behaviorally naive mice. We used BMS-204352, which has been shown to exhibit good bioavailability in the brain following intraperitoneal delivery 45 . Acute treatment with BMS-204352 (2 mg per kg of body weight) selectively eliminated the sensory hypersensitivity of Fmr1 −/y mice (P < 0.05) without affecting startle response in wild-type mice (Fig.…”
Section: Implication Of Bk Ca Channels In Dendritic Hyperexcitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed an exciting potential connection between the molecular alterations in FXS and startle habituation mechanisms: it has been shown that FMRP directly interacts with synaptic BK channels, which in turn have been shown to be crucial for short-term habituation (Deng et al, 2013; Hebert et al, 2014; Typlt et al, 2013b; Zhang et al, 2014). Unfortunately, startle habituation is not well studied in humans with FXS or Fmr1 ko mice, however, the allosteric BK channel activator BMS-204352 was shown to reverse behavioural and cellular FXS symptoms in Fmr1 ko mice (Hebert et al, 2014), highlighting the potential of studying sensory filtering mechanisms in animal models for developing pharmaceutical treatments.…”
Section: Sensory Processing In Rodent Models Relevant To Fxs and Asdmentioning
confidence: 99%
“…Of note, a recent study has identified a potential neuronal correlate of hyperarousal in the somatosensory cortex of Fmr1 KO mice that was rescued pharmacologically using a BK CA channel opener [98]. The same BK CA activator has been used previously to rescue behavioral impairments in the FXS mouse model [166], suggesting that neuronal network hyperexcitability is a useful phenotype to evaluate therapeutic strategies in FXS.…”
Section: Macro-orchidismmentioning
confidence: 99%